Powerful knowledge, disciplinary knowledge, curriculum knowledge: educational knowledge in question. Issue 1 (2nd January 2023) - Muller, Johan
Abstract: This paper traces the sociological roots of the 'knowledge turn' and a concept centrally identified with it, 'powerful knowledge', beginning with the work of Basil Bernstein which was subsequently elaborated in a wide range of contexts-of-use in the broad field of curriculum studies. The paper distinguishes different reasons educators have for engaging with curriculum which the paper classifies into 'curriculum of' and 'curriculum for'. It goes on to discuss the particular pathos of specialised knowledge, and suggests ways of dealing with it; and concludes by suggesting paths going forward for bringing curriculum theory and subject didactics into productive dialogue